Clinical Outcomes of In Vitro Maturation After Oocyte Retrieval With Gynecological Surgery for Refractory Polycystic Ovary Syndrome: A Retrospective Cohort Study - Zhang, Wen; Liang, Tingting; Han, Bing; Yang, Rui; Yang, Shuo; Yang, Yan; Zhang, Jiajia; Zheng, Xiaoying; Yan, Jie; Ma, Caihong; Song, Xueling; Qiao, Jie (Frontiers in Endocrinology, 2022)
Objective: To explore the clinical outcomes of unstimulated in vitro maturation (IVM) after oocyte retrieval with gynecological surgery (IVM-surgery) for refractory polycystic ovary syndrome (PCOS) and analyze the influencing factors. Methods: Patients with refractory PCOS who underwent unstimulated IVM-surgery from June 2014 to September 2018 were included in this retrospective cohort study. Matured IVM oocytes were freshly fertilized and subsequently frozen at the blastocyst stage. Frozen-thawed embryo transfer was then conducted according to the desire of patients. Oocytes and embryological outcomes, reproductive outcomes were evaluated. Influencing factors of oocytes and embryological outcomes were analyzed by univariate analysis and multivariate analysis. Receiver operating characteristic curves were used to evaluate the predict value of serum hormone levels for oocytes and embryological outcomes. Results: A total of 93 patients with refractory PCOS who underwent unstimulated IVM-surgery were included in this study.13 patients (13/85, 15.3%) had spontaneous pregnancy and live birth after surgery. 34 patients (34/93, 36.6%) obtained blastocysts and received embryo transfer, of which 13 patients (13/34, 38.2%) eventually achieved live birth by IVM. Higher anti-mullerian hormone, antral follicle count and basal serum luteinizing hormone (LH) levels were strongly correlated with higher number of oocytes retrieved (P = 0.004, 0.004, 0.040, respectively). Higher basal serum follicle-stimulating hormone (FSH) and LH were significantly associated with higher oocyte maturation rate (P = 0.001 and P = 0.004, respectively) and blastocyst formation (P = 0.036 and P = 0.003, respectively). There was a significant linear correlation between basal serum FSH and LH (r = 0.500, P <0.001). What is more, basal serum FSH and LH had predictive value for oocytes and embryological outcomes. Conclusions: Unstimulated IVM-surgery provided the opportunity for both spontaneous pregnancy and assisted reproductive technology. Basal FSH and LH were significantly associated with oocyte maturation rate and blastocyst formation of unstimulated IVM-surgery.